Pilot Observational Study to Detect Diurnal Variation and Misalignment in Heart Rate Among Critically Ill Patients - Knauert, Melissa P.; Murphy, Terrence E.; Doyle, Margaret M.; Pisani, Margaret A.; Redeker, Nancy S.; Yaggi, Henry K. (Frontiers in Neurology, 2020)
Circadian disruption is common in critically ill patients admitted to the intensive care unit (ICU). Understanding and treating circadian disruption in critical illness has significant potential to improve critical illness outcomes through improved cognitive, immune, cardiovascular, and metabolic function. Measurement of circadian alignment (i.e., circadian phase) can be resource-intensive as it requires frequent blood or urine sampling over 24 or more hours. Less cumbersome methods of assessing circadian alignment would advance investigations in this field. Thus, the objective of this study is to examine the feasibility of using continuous telemetry to assess diurnal variation in heart rate (HR) among MICU patients as a proxy for circadian alignment. In exploratory analyses, we tested for associations between misalignment of diurnal variation in HR and death during hospital admission. This was a prospective observational cohort study embedded within a prospective MICU biorepository. HR data were continuously collected (every 5 seconds) via telemetry systems for the duration of the MICU admission; the first 24 hours of this data was analyzed. Patients were extensively characterized via medical record chart abstraction and patient interviews. Of the 56 patients with complete HR data, 48 (86%) had a detectable diurnal variation. Of these patients with diurnal variation, 39 (81%) were characterized as having the nadir of their HR outside of the normal range of 02:00 to 06:00 (“misalignment”). Interestingly, no deaths occurred in the patients with normally aligned diurnal variation; in contrast, there were 7 deaths (out of 39 patients) in patients who had misaligned diurnal variation in HR. In an exploratory analysis, we found that the odds ratio of death for misaligned versus aligned patients was increased at 4.38; however, this difference was not statistically significant (95% confidence interval 0.20 – 97.63). We conclude that diurnal variation in HR can be detected via continuous telemetric monitoring of critically ill patients. A majority of these patients with diurnal variation exhibited misalignment in their first 24 hours of MICU admission. Exploratory analyses suggest possible associations between misalignment and death.